Frequency of Perforation Peritonitis Due to Typhoid: An Experience at a Tertiary Care Hospital in Balochistan - Amir Jogezai, Ruheen; Sasoli, Nazeer Ahmad; Karim, Samina; Farooq, Omer; ., Jahanara; Ahmad, Hassaan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine frequency of perforation peritonitis due to typhoid among the cases admitted in a tertiary care hospital in province Balochistan.Study Design: Cross-sectional study.Place and Duration of Study: Surgical Department, Sandeman Provincial Hospital, Quetta Pakistan, from Jan to Jun 2023.Methodology: This study was conducted on 140 cases of perforation peritonitis admitted in the surgical department of the hospital. Data was recorded regarding clinical presentation of the patients, cause of perforation, site of perforation, treatment given, postoperative complications and mortality rate. Patients of both genders and any age were included in this study. First of all patients were resuscitated in emergency department then exploratory laparotomy done to rule out the cause.Results: Most common cause of perforation was acid peptic disease in 58(41.4%) cases followed by typhoid in 40(28.5%) cases. The most common site of perforation was gastroduodenal in 58(41.4%), ileal in 51(36.4%), appendicular 16(11.4%), colonic 10(7.1%), and jejunal in 5(3.6%) cases. Age range of the cases was 15 to 75 years, with a mean age of 42.12±12.38 years. Study sample included 95(67.9%) male and 45(32.10%) female cases.Conclusion: Typhoid was the second most common cause of perforation peritonitis while acid peptic disease was on top among the causes in this study, while most common site of perforation was upper part of gastrointestinal tract.